2014
DOI: 10.1002/joc.4000
|View full text |Cite
|
Sign up to set email alerts
|

Variability in summer anticyclonic circulation over the Canadian Arctic Archipelago and west Greenland in the late 20th/early 21st centuries and its effect on glacier mass balance

Abstract: More frequent summer anticyclonic circulation over the Canadian Arctic Archipelago (CAA) between 2007 and 2012 caused more intense and sustained melt of ice caps and glaciers and increased rates of mass loss. To determine the frequency of the occurrence of anticyclonic circulation over the CAA and western Greenland, a self‐organizing map (SOM) was used to classify daily 500 hPa geopotential height (GPH) anomalies calculated from National Centers for Environmental Prediction and the National Center for Atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 84 publications
(182 reference statements)
4
42
0
Order By: Relevance
“…In addition, the atmospheric patterns associated with the summer SIEs in Baffin Bay, the Greenland Sea and Kara-Barents Seas are also characterised by the summer anticyclonic circulation. The summer anticyclonic anomalies over the Arctic and Greenland have been strong recently (Ogi and Wallace, 2012;Rajewicz and Marshall, 2014;Bezeau et al, 2015;Hanna et al, 2016). In the present study, the summer anticyclonic circulation has contributed to rapid fluctuations and trends in both summer GrSTs and SIEs surrounding Greenland.…”
Section: Summary and Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In addition, the atmospheric patterns associated with the summer SIEs in Baffin Bay, the Greenland Sea and Kara-Barents Seas are also characterised by the summer anticyclonic circulation. The summer anticyclonic anomalies over the Arctic and Greenland have been strong recently (Ogi and Wallace, 2012;Rajewicz and Marshall, 2014;Bezeau et al, 2015;Hanna et al, 2016). In the present study, the summer anticyclonic circulation has contributed to rapid fluctuations and trends in both summer GrSTs and SIEs surrounding Greenland.…”
Section: Summary and Discussionsupporting
confidence: 49%
“…Greenland blocking) than the summer NAO since the 1970s. Bezeau et al (2015) found that the strong summer anticyclonic circulation over the Canadian Arctic Archipelago and western Greenland is more frequent between 2007 and 2012 than from 1948 to 2006. Hanna et al (2016) showed that since 2007 there has been a significant increase in the occurrence of Greenland blocking during summer.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…While both the GrIS and sea ice environments are responding to anthropogenic warming (Hanna et al, 2008), changes in atmospheric circulation patterns that favor increased sea ice loss and GrIS melt have also played a role. Analysis of mid-tropospheric summer (JJA) sea level pressure (SLP) reveal statistically significant increases over Greenland and north of the Canadian Arctic Archipelago coupled with significant negative trends over northern Eurasia and Canada from 1979 to 2014 (Serreze et al, 2016;Bezeau et al, 2015), dominated by a clear shift in the last decade (2005 to 2014) towards large positive SLP anomalies over the central Arctic Ocean and Greenland. This pattern favors both summer sea ice loss (e.g., Wang et al, 2009;Ogi and Wallace, 2007) and Greenland surface melt (Hanna et al, 2013;Mioduszewski et al, 2016;Ballinger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…During the 2007-2012 period when the NAO index was negative (Fig. 8), there was an increase in the frequency of anticyclonic circulation, compared to the 1948-2012 mean (Bezeau et al, 2015). Similarly, over the Greenland Ice Sheet, strong anticyclonic ridging, associated with clear skies and the advection of warm air from the south, was found to co-vary with the NAO index over the period since ~2001 (Rajewicz and Marshall, 2014).…”
Section: Summer and Monthly Bsamentioning
confidence: 89%
“…7a) (Fig. 8), the frequency of anticyclonic circulation over the QEI in summer doubled relative to the 1948-2012 mean (Bezeau et al, 2015). Clear sky conditions that accompany anticyclonic circulation increase the proportion of incoming shortwave radiation received at the air-ice interface, providing more energy for melt and driving albedo decline.…”
Section: Principal Components Analysismentioning
confidence: 97%